A Systematic Literature Review Using the PRISMA Method: The Influence of Digital Leadership Across Sectors - Saputro, Arie Hendra; Santoso, Budi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to systematically examine the influence of digital leadership across various sectors using the PRISMA method (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The review focuses on identifying trends in research methodologies, geographical coverage, and the sectors in which digital leadership has been studied. A Systematic Literature Review (SLR) approach was employed, analyzing 31 Scopus-indexed articles published between 2020 and 2024. These articles were assessed based on the research methods used, the country of origin, and the sectoral focus. The analysis reveals that digital leadership contributes to enhancing organizational innovation, fostering a digital work culture, strengthening organizational commitment, and developing adaptive capabilities. Most studies adopted a quantitative approach and were conducted predominantly in Asia, particularly in Indonesia, Malaysia, and Saudi Arabia. These findings affirm that digital leadership is a strategic element crucial for supporting organizational transformation across sectors in the digital era. This study is expected to serve as a foundation for developing more contextual and applicable models of digital leadership.
Keywords: Digital Leadership; SLR; PRISMA; Industry